Minimally Invasive Versus open AbdominoThoracic Esophagectomy for esophageal carcinoma (MIVATE): study protocol for a randomized controlled trial DRKS00016773 - Nickel, Felix; Probst, Pascal; Studier-Fischer, Alexander; Nienhüser, Henrik; Pauly, Jana; Kowalewski, Karl-Friedrich; Weiterer, Sebastian; Knebel, Phillip; Diener, Markus K.; Weigand, Markus A.; Büchler, Markus W.; Schmidt, Thomas; et al. (Trials, 2021)
The only curative treatment for most esophageal cancers is radical esophagectomy. Minimally invasive esophagectomy (MIE) aims to reduce postoperative morbidity, but is not yet widely established. Linear stapled anastomosis is a promising technique for MIE because it is quite feasible even without robotic assistance. The aim of the present study is to compare total MIE with linear stapled anastomosis to open esophagectomy (OE) with circular stapled anastomosis with special regard to postoperative morbidity in an expertise-based randomized controlled trial (RCT).